MAIN ASPECTS OF COMPETENCY-BASED EDUCATION (World Bulletin of Public Health, 2026)
This article provides a comprehensive analysis of the theoretical and practical aspects of education organized on the basis of a competencybased approach. In particular, it examines the types of professional and practical competencies, as well as the mechanisms of their formation and stage-by-stage development on a scientific and methodological basis
Keywords: competence; assessment; information